Cryogenic fuel storage modelling and optimisation for aircraft applications - Rompokos, Pavlos; Rolt, Andrew Martin; Nalianda, Devaiah; Sibilli, Thierry; Benson, Claire (American Society of Mechanical Engineers (ASME), 2021)
Designing commercial aircraft to use liquid hydrogen (LH2) is one way to substantially reduce their life-cycle CO2 emissions. The merits of hydrogen as an aviation fuel have long been recognized, however, the handling of a cryogenic fuel adds complexity to aircraft and engine systems, operations, maintenance and storage. The fuel tanks could account for 8–10% of an aircraft’s operating empty weight, so designing them for the least added weight is of high significance. This paper describes the heat transfer model developed in the EU Horizon 2020 project that is used to predict heat ingress to a cylindrical tank with hemispherical end caps with external foam insulation. It accounts for heat transfer according to the state of the tank contents, the insulation material properties, the environment, and the dimensions of the tank. The model also estimates the rate of pressure change according to the state of the fuel and the rate at which fuel is withdrawn from the tank. In addition, a methodology is presented, that allows for tank sizing taking into consideration the requirements of a design flight mission, the maximum pressure developed, and the fuel evaporated. Finally, the study demonstrates how to select optimal insulation material and thickness to provide the lightest design for the cases where no gaseous hydrogen is extracted, and where some hydrogen gas is extracted during cruise, the latter giving gravimetric efficiencies as high as 74%.
Keywords: hydrogen; alternative energy sources; aerospace applications; heat transfer